Lycopene supplementation prevents the development of spontaneous smooth muscle tumors of the oviduct in Japanese quail - Şahin, Kazım; Ozercan, R; Onderci, M; Şahin, Nurhan; Gursu, MF; Khachik, F; Küçük, Ömer (Routledge Journals, Taylor & Francis Ltd, 2004)
Leiomyomas (fibroids) are benign tumors of the uterus affecting millions of women. Spontaneous leiomyomas of the oviduct are common tumors of the Japanese quail (Coturnix coturnix japonica), which makes it a good animal model for screening potential agents for testing in the prevention and treatment of human m myoma uteri. Because dietary intake of lycopene has been associated with a reduced risk of a variety of human cancers, we investigated the effects of lycopene supplementation on the development of leiomyomas in the oviduct of Japanese quail. We also measured serum levels of oxidative stress markers [,malondialdehyde (MDA) and homocysteine], lycopene, vitamins C, E, and A, and tissue biomarkers Bcl-2 and Bax expression. One hundred twenty quails (6mo old) were assigned to 3 treatment groups consisting of 4 replicates of 10 birds in each group. Birds were fed either a basal diet (group C) or the basal diet supplemented with 100 mg (group L1) or 200 mg (group L2) of lycopene per kilogram of diet. The animals were sacrificed after 285 days and the tumors were identified. Lycopene supplementation decreased the number of leiomyomas compared with control subjects (P = 0.056). The tumors in lycopene-fed birds were smaller than those found in control birds (P = 0.01). There were no significant differences in the expression of tissue Bcl-2 and Bax among the study groups. Serum vitamins C, E, and A increased (P = 0.01), whereas MDA and homocysteine concentrations decreased (P = 0.01) with lycopene supplementation. No measurable lycopene could be detected in the serum of control birds, whereas a dose-dependent increase was observed in the serum of lycopene-supplemented birds. The results indicate that dietary supplementation with lycopene reduces the incidence and Size of spontaneously occurring leiomyoma of the oviduct in the Japanese quail. Clinical trials should be conducted to investigate the efficacy of lycopene supplementation in the prevention and treatment Of uterine leiomyoma in humans.
Keywords: Gap Junctional Communication; Vivo Antioxidant Properties; Cell-Cycle Progression; Growth-Factor-I; Prostate-Cancer; Lipid-Peroxidation; Neoplastic Transformation; Uterine Leiomyomas; Tomato Consumption; Oxidative Damage